Vialidad, Transporte y Planeamiento urbano-regional en Santiago de Chile, 1950-1979 - Pávez Reyes, María Isabel (Cuadernos de Investigación Urbanística, 2007)
Se refiere los conceptos modernos Vialidad y Transporte (V.T.) que informan las obras 1950–1979 para Santiago en el marco de los 50 años del Estado Planificador (1929-1979). Se sostiene en esta tesis que:• La gestación de los conceptos modernos de V.T. se habría originado en el cuerpo de arquitectos chilenos dedicados a la Planificación Urbana y Regional (P.U.R.), los que fueron reflexivos y críticos respecto de parte de los enunciados del Movimiento Moderno, y consideraron las redes viales como un principio de ordenamiento territorial relacionando las posibilidades técnicas con el servicio de las regiones urbanas • La obra 1950-1979 en V.T. habría sido coherente con las formas coordinadas de crecimiento propuestas para Santiago en la intercomuna y en la región por la P.U.R. 1950-1979, constituyendo un sistema estructurante debidamente conectado al territorio nacional, contribuyendo a configurar una región urbana moderna que consideró todos sus ámbitos como un “interior” en la perspectiva del funcionamiento del sistema sin derroche de recursos, y de su permanencia a lo largo del tiempo • La concepción tras la obra 1950-1979, habría previsto su proyección sobre una macroregión andina central , binacional trinucleada -comprendiendo Santiago, Valparaíso y Mendoza, esta última en la república Argentina-, la cual tiene como eje fundamental el Corredor Transandino Central Valparaíso-Buenos Aires • Y que, desde los años 1990, la obra 1950-1979 para Santiago está siendo objeto de proyectos en torno a los cuales está teniendo lugar una nueva y diferente fase del proceso metropolización, la que está desplegando a la población sobre su región generando islas de suelo urbano, mas no ciudad. La narración demostrativa se organiza en torno a cinco procesos en interacción: de urbanización, de industrialización, de profesionalización de las disciplinas de interés, de planificación urbana y regional y de planificación del transporte metropolitano en Santiago de Chile. Abstract: The thesis describes and interprets the work of Road Network and Transport 1950–1979 - in the frame of 50 years of the Planning State (1929-1979)- in its capacity to contribute both to order the territory of the Inter communal and the region of Santiago, as well as the Interregion formed by Valparaíso-Santiago (Chile), and Mendoza (Argentina) with a time horizon to the year 2000, contributing in this way to the discussion about the value of this experience of the Planning State of Chile. The hypothesis state: • That the preparation of the modern concepts of Roar Network and Transport had arisen from the group of Chilean architects devoted to Urban and Regional planning, which were thoughtful and critical with respect to part of the doctrines of the Modern Movement, and considered the road networks as the starting point for the territorial ordering relating the technical possibilities with the service of the Chilean urban regions. • That the work 1950-1979 in Road Network and Transport had been coherent with the coordinated growing forms proposed for the metropolis of Santiago in the inter-commune and in the region by the Urban and Regional Vialidad y Transporte en la Metrópolis de Santiago - nº 51 - marzo / abril 2007 5 Planning 1950-1979, becoming a structuring system properly connected to the national territory, and that would allow the access to the new human settlements metropolitan equipment prepared in the urban and regional territory, contributing to configure a modern urban region since it considered all its aspects as an “interior” from the point of view of sustainability and duration as a whole. • That the concept behind the work 1950-1979, had foreseen its projection on a central macro region of Chile, for being immersed in a bi national economy of three nucleuses, that considered Santiago, Valparaíso and Mendoza, the later in Argentina, which has the Corredor Transandino Central Valparaíso-Buenos Aires as the fundamental axle. • And that, from 1990, the work 1950-1979 for Santiago is object of future projects around which a new phase of the metropolitan process is taking place, which is deploying the population on the territory of its region.- The narration, structured around five interacting processes -urbanization, industrialization, professionalization of the disciplines of interest, urban and regional planning and metropolitan transport planning in Chile-, it succeeds in demonstrating the hypothesis.